মঙাল - (:unkn) unknown (My University, 2019)
This Volume is an Advanced Course reader in Manipuri language for Diploma in Language Education. As per syllabus of CIIL, this Reader includes various domains of literature viz., short story, poem, drama, travelogue, essay, humorous essay, biography, auto biography, etc. Most of the topics are selected from the writings of Sahitya Akademi awardees.
Mangaal-An advanced course reader in Manipuri
Keywords: Manipuri